Pembuatan Keripik Dari Pelepah Pisang Kepok (Kajian Konsentrasi Kapur Sirih dan Lama Perendaman) - Nopriyanti, Marisa; Arahman, Emy; Adimarta, Trian; Doni Idola, Antonius (Jurnal Teknologi Pangan dan Industri Perkebunan (LIPIDA), 2024)
This research aims to determine the results of chemical analysis (water content and ash content tests) and organoleptic tests (hedonic test and ranking test) of chips from Kepok banana stems. The method for making kepok banana frond chips is washing, slicing, soaking, frying and packaging with a comparison of the effect of whiting concentration (5%, 7.5% and 10%) and soaking time (48 hours, 36 hours and 24 hours) on results of chemical analysis and physical analysis of kepok banana stem chips. The results of the research showed that the chemical test for water content in treatment 1 with a 5% whiting concentration and a soaking time of 48 hours was 5.65%. The results of water content analysis in treatments 2 and 3 with whiting concentration (7.5% and 10%) and soaking time (36 hours and 24 hours) were 9.9923 and 8.1286. The results of the ash content test using the concentration of betel lime (5%, 7.5% and 10%) and the soaking time (48 hours, 36 hours and 24 hours) resulted in ash content of 1.02%, 0.86% and 1.49 % already meets SNI for Banana Chips ash content. The results of the physical analysis of the organoleptic test (Hedonic Test) of taste parameters were very significantly different at the 0.5% and 0.1% levels so it was necessary to carry out further Duncan tests. The results of the organoleptic test (Rank Test) produced color and texture parameters that were not significantly different at the 0.5% and 0.1% levels.